Research methods for forensic psychologists : - Brown, Sarah (Routledge, Taylor & Francis Group, 2016)
Research Methods for Forensic Psychologists is an accessible and comprehensive textbook that introduces students to the research process in forensic psychology. Adopting a problem-based learning approach, this book offers a ‘how-to’ guide to the whole research process and empowers readers to develop their own programme of research, from initial vague ideas, to developing a research question, to carrying out a methodologically rigorous research project, to disseminating the findings.